2021
DOI: 10.1111/ejn.15372
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular matrix alterations in mediating astrocyte damage and pericyte dysfunction in Alzheimer's disease: A comprehensive review

Abstract: The brain is a highly vascularized tissue protected by the blood-brain barrier (BBB), a complex structure allowing only necessary substances to pass through into the brain while limiting the entrance of harmful toxins. The BBB comprises several components, and the most prominent features are tight junctions between endothelial cells (ECs), which are further wrapped in a layer of pericytes. Pericytes are multitasked cells embedded in a thick basement membrane (BM) that consists of a fibrous extracellular matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 157 publications
0
23
0
Order By: Relevance
“…While our gene association analysis suggested that it is involved in stress response and neuropeptide signaling, there is not a clear mechanistic link to AD pathology. One possible mechanism for how ADAMTS2 modifies AD risk could be through dysregulated extracellular matrices, and like PRTN3 , affecting blood-brain-barrier integrity ( Anwar et al, 2021 ). In a related role, ADAMTS2 can cleave and inactivate reelin ( Yamakage et al, 2019 ), an extracellular matrix protein that is important for synaptic plasticity ( Bock and May, 2016 ; Lussier et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…While our gene association analysis suggested that it is involved in stress response and neuropeptide signaling, there is not a clear mechanistic link to AD pathology. One possible mechanism for how ADAMTS2 modifies AD risk could be through dysregulated extracellular matrices, and like PRTN3 , affecting blood-brain-barrier integrity ( Anwar et al, 2021 ). In a related role, ADAMTS2 can cleave and inactivate reelin ( Yamakage et al, 2019 ), an extracellular matrix protein that is important for synaptic plasticity ( Bock and May, 2016 ; Lussier et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…GO analysis of downregulated genes in these groups also showed functional changes in ‘extracellular space’ and ‘extracellular region’, suggesting an imbalance in synthesis and degradation of extracellular components of hippocampal tissue during the early and middle stages of CUMS. This imbalance might cause excessive deposition of ECM components in the hippocampal tissue ( 35 ), such as collagen, metalloproteinase, fibronectin, bone morphogenetic protein 7, nidogen 1 and elastin, which contributes to development of organ fibrosis ( 36 ). Collagen is a primary structural component of ECM and serves a key role in the cell cycle stimulated by mitogen ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of collagen fibers serve an important role in tissue injury healing ( 42 , 43 ). Activation of ECM in the hippocampus during the early and middle stages of CUMS is hypothesized to contribute to self-repair of damaged hippocampal cells but also promotes hippocampal sclerosis, which leads to partial neuronal loss ( 35 ). ECM changes are often secondary to inflammatory reactions ( 36 ), which indicates that hippocampal inflammation occurs during the early and middle stages of CUMS.…”
Section: Discussionmentioning
confidence: 99%
“…The cortical thickness was also found to be attenuated with elevated IL-6 level indicating general cortical atrophy ( McCarrey et al, 2014 ) ( Table-1 ). These observed changes can be considered a consequence of the onset of AD-associated progressive damage ( Miralbell et al, 2012 , Anwar et al, 2021b ) ( Table-1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, high serum TNF-α level was found to be associated with alterations in the gray matter GM structural volume as stemming from inflammatory cascades and the exaggerated release of inflammatory type microglia-M1 ( Taishi et al, 2007 ; Benson et al, 2020 ; Anwar et al, 2021a , Anwar et al, 2021b ) ( Table-1 ). Additionally, exploratory examination of the volume of subcortical structures revealed inverse association of inflammation with volumes of the hippocampus, pallidum, and thalamus, where these findings also support the inverse associations of inflammatory markers with both global measures of gray matter volume/white matter integrity, and with regional gray matter volume of the hippocampus among healthy midlife adults ( Marsland et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%